Th17-Immune Response in Patients With Membranous Nephropathy Is Associated With Thrombosis and Relapses - Cremoni, Marion; Brglez, Vesna; Perez, Sandra; Decoupigny, Fabrice; Zorzi, Kévin; Andreani, Marine; Gérard, Alexandre; Boyer-Suavet, Sonia; Ruetsch, Caroline; Benzaken, Sylvia; Esnault, Vincent; Seitz-Polski, Barbara (Frontiers in Immunology, 2020)
Membranous nephropathy (MN) is a rare autoimmune kidney disease. Most autoimmune diseases are associated with a pro-inflammatory Th17-immune response, but little is known about immune dysregulation in MN. In China, MN was associated with exposure to fine air particulate matter (PM2.5) that could act as a danger signal and redirect immune response towards the Th2 or Th17 pathway. We aimed to analyze the cytokine profile of MN patients and to study the possible environmental factors involved in this immune reorientation, as well as the consequences on the prognosis of the disease. In this prospective study, 59 MN patients filled a comprehensive lifestyle questionnaire. Peripheral blood cells from MN patients were stimulated in vitro to measure the cytokines produced in supernatant. Cytokine profiles of MN patients were compared to 28 healthy donors and analyzed regarding individual PM2.5 exposure. Compared to healthy donors, MN patients had higher serum levels of Th17 and Th2 cytokines IL-17A (62 pg/mL [IQR, 16–160] versus 31 [IQR, 13–51], P=0.035), IL-6 (66767 pg/mL [IQR, 36860–120978] versus 27979 [IQR, 18672–51499], P=0.001), and IL-4 (12 pg/mL [IQR, 0–33] versus 0 pg/mL [IQR, 0–0], P=0.0003), respectively, as well as a deficiency of Th1 and regulatory T cell cytokines IFN-γ (5320 pg/mL [IQR, 501–14325] versus 18037 [IQR, 4889–31329], P=0.0005) and IL-10 (778 pg/mL [IQR, 340–1247] versus 1102 [IQR, 737–1652], P=0.04), respectively. MN patients with high IL-17A levels lived in areas highly exposed to PM2.5: 51 μg/m3 versus 31 μg/m3 for patients with low IL-17A levels (P=0.002) while the World Health Organization recommends an exposition below 10 μg/m3. MN patients with Th17-mediated inflammation had more venous thromboembolic events (P=0.03) and relapsed more often (P=0.0006). Rituximab treatment induced Th1 and regulatory T cell cytokines but did not impact Th17 cytokines. MN patients with Th17-mediated inflammation which appears to be related to an urban environment have worse prognosis. Alternative strategies targeting dysregulated cytokine balance could be considered for these patients at high risk of relapse.